Evaluasi Kinerja Keuangan BAZNAS Republik Indonesia Menggunakan Rasio Keuangan Syariah : Periode 2019–2021 - Iqrima Mas Mappangile; Syahrial Maulana (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to evaluate the financial performance of the National Amil Zakat Agency (BAZNAS) of the Republic of Indonesia during the period 2019–2021 using Islamic financial ratios as the primary analytical tool. The assessment focuses on four key ratios: liquidity, solvency, amil fund efficiency, and activity, to measure the effectiveness, efficiency, and Sharia compliance in managing zakat, infaq, and sadaqah funds. The findings show that BAZNAS maintained high liquidity levels, though this was partly due to idle funds resulting from delays in fund distribution. Solvency ratios significantly declined in 2021, primarily due to the overutilization of amil funds exceeding Sharia limits. Although amil fund management was generally efficient and within the prescribed thresholds, weaknesses were found in budget control and operational management. Activity ratios indicated a positive trend in fund distribution, supported by the implementation of the SIMBA (BAZNAS Management Information System) technology. The study concludes that BAZNAS must enhance transparency, improve fund distribution efficiency, and strengthen internal controls to optimize its role in empowering the ummah in accordance with Sharia principles.